TINDAK DIREKTIF BAHASA INDONESIA DALAM WACANA KELAS SEKOLAH DASAR - Alif Mudiono (Fakultas Sastra Universitas Negeri Malang, 2013)
This study is focused on (1) the directive acts in Indonesian elementary classroom discourse, and (2) the impact of its use in classroom settings. The method used in this study was ethnography and pragmatics approach. The results of the dataanalysis are as follows (1) the directive acts in elementary school settings include the actof ordering, asking, encouraging, questioning, and directing, and(2) the impacts of its are silent response, doing the task according to the provision of the command, as well as the attitudes of students who are willing to respond to and be responsive to the learning process.